Clinical impact of skin lesions in mastocytosis: a multicenter study of the european competence network on mastocytosis - Aberer, Elisabeth; Sperr, Wolfgang R.; Bretterklieber, Agnes; Avian, Alexander; Hadzijusufovic, Emir; Kluin-Nelemans, Hanneke C.; Oude Elberink, Hanneke; van Anrooij, Björn; Niedoszytko, Marek; Lange, Magdalena; Górska, Aleksandra; Elena, Chiara; et al. (The journal of investigative dermatology, 2021)
Mastocytosis is a rare neoplasm characterized by the expansion and accumulation of mast cells in various organ systems. Systemic mastocytosis (SM) may or may not present with cutaneous lesions. To examine the frequency and clinical impact of cutaneous involvement, data on 1,510 patients with mastocytosis collected in the registry of the European Competence Network on Mastocytosis were analyzed. Cutaneous involvement was found in 1,195 of 1,510 patients (79.1%). Of these, 286 had cutaneous mastocytosis, and 721 had SM with skin involvement. Adult patients with skin involvement who did not have a bone marrow examination (n = 188) were defined as having mastocytosis in the skin. In 315 patients, SM without skin involvement was found. The percentage of cases with cutaneous involvement was higher in indolent SM (100%) and smoldering SM (87.9%) compared to aggressive SM (46.8%) or mast cell leukemia (38.5%). After a median follow-up of 5.6 years, no patient with cutaneous mastocytosis had died, but 2.6% of the patients with mastocytosis in the skin, 5.7% of the patients with SM with skin involvement, and 28.95% of the patients with SM without skin involvement had died. Overall survival was longer in patients with skin involvement (cutaneous mastocytosis and/or mastocytosis in the skin and/or SM with skin involvement) than in patients with SM without skin involvement (P < 0.0001). These data argue for a thorough examination of both the skin and bone marrow in adult patients with mastocytosis.